Assessment of Socio-Economic Development Forecast for the Russian Federation in 2019–2024 - artiсle Editorial (Финансы: теория и практика)
This paper presents the conclusion of the Financial university expert group on the socio-economic development forecast for the Russian Federation in 2019–2024 (developed by the Ministry of Economic Development of Russia). The forecast has been evaluated according to the task set in the Decree of the President of the Russian Federation on May 7, 2018 No. 204 “On National Goals and Strategic Objectives of the Russian Federation through to 2024”, regarding achievement breakthroughs in science and technology and socioeconomic development in the Russian Federation. Special attention has been paid to the analysis of forecasted rates and projected sources of economic growth and prospects for social development. According to the analysis, it has been concluded that the proposed forecast indicators are not adequate to the task of “achievement breakthroughs in science and technology and socioeconomic development in the Russian Federation”, provided by the Decree of the President of Russia of May 7, 2018, No. 204.